Brachiaria Grasses (Brachiaria spp.) harbor a diverse bacterial community with multiple attributes beneficial to plant growth and development - Mutai, C.; Njuguna, J.; Ghimire, Sita R. (Wiley, 2017)
Endophytic and plant‐associated bacteria were isolated from plants and rhizoplane soil of naturally grown Brachiaria grasses at International Livestock Research Institute in Nairobi, Kenya. Eighty‐four bacterial strains were isolated from leaf tissues, root tissues, and rhizoplane soil on nutrient agar and 869 media. All bacterial strains were identified to the lowest possible taxonomic unit using 16S rDNA primers and were characterized for the production of Indole‐3‐acetic acid, hydrogen cyanide, and ACC deaminase; phosphate solubilization; siderophore production; antifungal properties; and plant biomass production. The 16S rDNA‐based identification grouped these 84 bacterial strains into 3 phyla, 5 classes, 8 orders, 12 families, 16 genera, and 50 unique taxa. The four most frequently isolated genera were Pseudomonas (23), Pantoea (17), Acinetobacter (9), and Enterobacter (8). The functional characterization of these strains revealed that 41 of 84 strains had a minimum of three plant beneficial properties. Inoculation of maize seedlings with Acinetobacter spp., Microbacterium spp., Pectobacterium spp., Pseudomonas spp., and Enterobacter spp. showed positive effects on seedling biomass production. The ability of Brachiaria grasses to host genetically diverse bacteria, many of them with multiple plant growth‐promoting attributes, might have contributed to high biomass production and adaptation of Brachiaria grasses to drought and low fertility soils.